2021
DOI: 10.3390/f12040394
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Urban Forest Types and Traits on Soil Organic Carbon Stock in Beijing

Abstract: Forests can affect soil organic carbon (SOC) quality and distribution through forest types and traits. However, much less is known about the influence of urban forests on SOC, especially in the effects of different forest types, such as coniferous and broadleaved forests. Our objectives were to assess the effects of urban forest types on the variability of SOC content (SOC concentration (SOCC) and SOC density (SOCD)) and determine the key forest traits influencing SOC. Data from 168 urban forest plots of conif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 73 publications
(73 reference statements)
1
9
0
Order By: Relevance
“…Suffice to say that there was a partial and varied soil type × AVC interaction across all levels. Correspondingly, studies by Setala et al [68] and Xu et al [69] reported similar interactions between soil types and vegetation types. They established that vegetation types, greatly modify the soil biogeochemistry of pH, %OM, %C, and %N and the C/N ratio, translating to significant variation in soil properties and processes among the vegetation types.…”
Section: To What Extent Do Soil Types And/ or Avc Act As Major Regula...supporting
confidence: 58%
“…Suffice to say that there was a partial and varied soil type × AVC interaction across all levels. Correspondingly, studies by Setala et al [68] and Xu et al [69] reported similar interactions between soil types and vegetation types. They established that vegetation types, greatly modify the soil biogeochemistry of pH, %OM, %C, and %N and the C/N ratio, translating to significant variation in soil properties and processes among the vegetation types.…”
Section: To What Extent Do Soil Types And/ or Avc Act As Major Regula...supporting
confidence: 58%
“…The included studies examined soil carbon using both direct and indirect approaches. Direct studies explicitly focused on carbon stock analysis in urban green areas [4,17,18,21,25,28,[48][49][50][51][52][53][54][55][56][57][58][59][60][61]. The indirect studies deviated from a specific focus on soil carbon as a central theme.…”
Section: Methodologies Used In the Reviewed Articles On Soil Carbon I...mentioning
confidence: 99%
“…As mentioned in the introduction, a predominant focus on soil carbon has been studied in the form of SOC [1,2,4,[16][17][18][19]21,22,[26][27][28][29]43,45,[48][49][50][51][52][54][55][56][57][58][59][60][61][62]65,67,[69][70][71][72]74,76,[80][81][82][83] and in the form of Total Carbon [25,50,51,63,65,66,68,73,75,[77]…”
Section: Methodologies Used In the Reviewed Articles On Soil Carbon I...mentioning
confidence: 99%
“…In forest ecosystems, plants provide primary C input into the soil, where leaf litter is decomposed to form humus and SOC by the action of microbes or abiotic polymerization (Zhou et al, 2015 ; Shi et al, 2018 ). Urban forests can provide many ecosystem services, such as improving air quality, sustaining biodiversity, and increasing C fixation (Roeland et al, 2019 ; Xu et al, 2021 ). In addition, urban forests also affect organic carbon components and then maintain ecosystem stability and mitigate climate change, thereby improving urban living quality and environments (Wang et al, 2023 ).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, urban forests also affect organic carbon components and then maintain ecosystem stability and mitigate climate change, thereby improving urban living quality and environments (Wang et al, 2023 ). Different urban forest planting patterns have different dominant plant species and compositions, resulting in variations in the substrate composition and quality of litter, soil properties, and microbial communities (Xu et al, 2021 ). Mixed-species forests with multiple species increase tree species diversity and improve the likelihood of finding species with complementary functional features for maximizing resource usage, according to the niche complementary hypothesis (Cassart et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%